Validating the inactivation of viral pathogens with a focus on SARS-CoV-2 to safely transfer samples from high-containment laboratories - Chaki, Sankar Prasad; Kahl-McDonagh, Melissa M.; Neuman, Benjamin W.; Zuelke, Kurt A. (Frontiers in Cellular and Infection Microbiology, 2024)
Pathogen leak from a high-containment laboratory seriously threatens human safety, animal welfare, and environmental security. Transportation of pathogens from a higher (BSL4 or BSL3) to a lower (BSL2) containment laboratory for downstream experimentation requires complete pathogen inactivation, for which validation of pathogen inactivation is necessary to ensure complete inactivation for safe transportation. This study established a validation strategy of viral pathogen inactivation by monitoring heat-inactivated SARS-CoV-2 viral titer over time and cytopathic effects in A549-hACE2 and Vero E6-TMPRSS2-T2A-ACE2 cell culture models. This validation procedure can be adapted with other viral pathogens in high-containment laboratories to enhance the biosecurity of sample transportation for downstream experimentations.